UNRAVELLING THE BIOCHEMICAL WEB: INSIGHTS INTO PATHOGENS AND RESISTANCE IN LOWER RESPIRATORY INFECTIONS - Hafiz Zeeshan Sadiq; Muhammad Asim Rana; Ahmed Hossameldin Ahmed Awad; Muhammad Ahmed; Bushra Arif; Ahmed M Abdelbaky; Wael Ghaly Elmasry (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Lower respiratory tract infections (LRTIs) are a major cause of morbidity and mortality, particularly in intensive care unit (ICU) patients. Identifying the causative pathogens and understanding antimicrobial resistance (AMR) patterns is critical for optimising treatment and improving patient outcomes. Objective: This study used bronchoalveolar lavage (BAL) samples in ICU settings to investigate the prevalence of infectious pathogens and antimicrobial resistance in patients with LRTIs. Methods: BAL samples were collected from ICU patients with LRTIs and analysed for bacterial, viral, and fungal pathogens. Biochemical tests and molecular techniques were employed to identify pathogens and detect antimicrobial resistance genes, including CTX-M, OXA-48-like, and NDM. Results: The study revealed that Klebsiella pneumoniae, Escherichia coli, and Human Rhinovirus/Enterovirus were the significant causative microorganisms in LRTIs. Fungal pathogens were infrequent in the analysed samples. A high prevalence of antimicrobial resistance genes, including CTX-M, OXA-48-like, and NDM, was detected in most samples, indicating significant multidrug resistance among the bacterial pathogens. Conclusion: The findings highlight the critical need for antimicrobial stewardship, the use of rapid diagnostic techniques, and the development of targeted antimicrobial therapies to manage LRTIs effectively in ICU patients. Addressing the high prevalence of AMR genes is essential for improving infection control strategies and patient outcomes at the local level.